SYSTEMIC SCLEROSIS AND CARDIOVASCULAR RISK: A SYSTEMATIC REVIEW OF ITS ASSOCIATION WITH ATHEROSCLEROSIS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular dysfunction, fibrosis, and immune dysregulation, leading to increased cardiovascular risk, including atherosclerosis and endothelial dysfunction. Despite growing evidence, the relationship between SSc and macrovascular complications remains unclear, necessitating a comprehensive review of existing literature. Objective: Analysis of the relationship between systemic sclerosis and cardiovascular diseases, and assessment of the role of biomarkers, AI diagnostics, and targeted therapy in managing these risks. Methods: This systematic review was conducted following PRISMA guidelines, analysing studies from PubMed, Scopus, Web of Science, Russian databases, and Google Scholar. A total of 18 studies were identified, and 12 were included based on predefined eligibility criteria. Studies evaluating cardiovascular risk, biomarkers, AI-based diagnostics, and therapeutic interventions in SSc were analysed. Results: Findings indicate that SSc is strongly associated with increased cardiovascular risk, primarily due to endothelial dysfunction, chronic inflammation, and immune-mediated vascular injury. AI-driven imaging and deep learning models demonstrated enhanced detection of vascular abnormalities, while elevated carotid intima-media thickness (IMT), coronary calcification, and lipoprotein (a) levels suggest a heightened atherosclerotic burden in SSc patients. Additionally, inflammatory markers (IL-6, TNF-α, and low complement 4) were linked to vascular damage, reinforcing the immune-mediated component of cardiovascular risk in SSc. Therapeutic interventions, including Endothelin-1 antagonists, showed potential in reducing oxidative stress and improving vascular function. However, despite these advancements, routine cardiovascular screening in SSc remains inconsistent, and more longitudinal studies are needed to evaluate the long-term impact of these interventions. Conclusion: SSc patients face significant cardiovascular risks, emphasizing the need for early screening, AI-driven diagnostics, and targeted interventions. Given the lack of standardized cardiovascular screening guidelines in SSc, further large-scale prospective studies and randomized controlled trials (RCTs) are essential to establish effective risk assessment and treatment strategies.